2020
DOI: 10.1155/2020/9641284
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Composition and Bioactivities of Essential Oils from Fresh and Dry Rhizomes of Zingiber zerumbet (L.) Smith

Abstract: The chemical constituents and the antioxidant, antimicrobial, and cytotoxic activities of fresh rhizome essential oil (FR-EO) and dry rhizome essential oil (DR-EO) of Zingiber zerumbet (L.) Smith obtained from Southwest China were compared. Zerumbone was the predominant component in both FR-EO and DR-EO (75.0% and 41.9%, respectively). FR-EO, DR-EO, and zerumbone were all demonstrated to have significant antimicrobial capacity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Proteus vulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
2
18
1
Order By: Relevance
“…The result of this study was found far better than the previous reports of Tian et al. (2020) and Padalia et al. (2018), whereby they demonstrated the antimicrobial capacity of Z. zerumbet EO collected from Guangxi Province (China) against Staphylococcus aureus , Bacillus subtilis , Escherichia coli , and Proteus vulgaris with MIC ranging from 78.13 to 156.25 µg/mL and antagonistic activity of Z. zerumbet EO isolated from rhizome collected from Pantnagar (India) against Staphylococcus aureus‐96, Streptococcus mutans , and E. coli with MIC ranging from 52.0 to 208.0 µg/mL, respectively.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…The result of this study was found far better than the previous reports of Tian et al. (2020) and Padalia et al. (2018), whereby they demonstrated the antimicrobial capacity of Z. zerumbet EO collected from Guangxi Province (China) against Staphylococcus aureus , Bacillus subtilis , Escherichia coli , and Proteus vulgaris with MIC ranging from 78.13 to 156.25 µg/mL and antagonistic activity of Z. zerumbet EO isolated from rhizome collected from Pantnagar (India) against Staphylococcus aureus‐96, Streptococcus mutans , and E. coli with MIC ranging from 52.0 to 208.0 µg/mL, respectively.…”
Section: Resultscontrasting
confidence: 95%
“…Such variability in chemical composition of a same EO might be due to differences in physiological adaptations, geographical conditions, harvesting time, plant parts used, and method of extraction (Deepika, Singh et al., 2020). The efficacy of ZEO was reported by many authors (Padalia et al., 2018; Tian et al., 2020); however, their poor solubility and instability against environmental causes may limit its long‐term application in food system (Beyki et al., 2014). A number of published studies reported that the nanoencapsulation in form of nanoemulsion is an effective approach to overcome these limitations (Chang, McLandsborough & McClements, 2015; Shishir, Xie, Sun, Zheng, & Chen, 2018).…”
Section: Resultsmentioning
confidence: 98%
“…The cytotoxic effect was assayed according to our previously published MTT method ( Tian et al., 2020 ) against murine fibroblast cell line (L929) and five human cell lines: fetal lung fibroblasts (MRC-5), lung adenocarcinoma (A549), and non-small cell lung cancer (NCI-H1299), prostatic carcinoma (PC-3), and leukemic (K562) cell lines. EO solution (0.1% DMSO), WE, and EE distilled water solution were two-fold serially diluted with medium.…”
Section: Methodsmentioning
confidence: 99%
“…IC50 (24h) of Lavandula stoechas against different cell lines were reported as MV3 0.01, MDA-MB231 0.25, and AGS 0.03 µg/mL 69 . Also, IC50 of Pinus eldarica with an exposure time of 48h against HeLa is 0.03 µg/mL 65 .…”
Section: Documentation Of the Anticancer Properties Of Eosmentioning
confidence: 96%
“…For instance, in Tables 3-7, some EOs with excellent anticancer activities (IC50: < 1 µg/mL) against at least a cancer cell are observable. They include Pinus eldarica 65 , Pallenis spinosa 66 , Pallines spinosa 67 , Foeniculum vulgare 76 , Oliveria decumbens 68 151 . Mentioned EOs appear to be good candidates, and their anticancer activity should be evaluated against commercial drugs.…”
Section: Future Perspectivesmentioning
confidence: 99%